Valorization of malaysian tropical fruit seeds: A review of their nutrition, bioactivity, processing and food application - Md Sani, Anis Nasuha; Mohd Adzahan, Noranizan; Ismail-Fitry, Mohammad Rashedi (Elsevier BV, 2022)
Malaysia produces varieties of tropical fruits such as durian, rambutan, jackfruit, mango, papaya, and mangosteen but the seeds are considered waste. The seeds contain beneficial nutrients such as protein, carbohydrates, fat, and minerals, and have high bioactive properties. Various processing methods have been applied to extract the seeds and apply them to the food system. The information is scattered and incomprehensive, therefore, this paper aims to review the chemical properties and biological activities of the selected tropical fruit seeds, and their processing and functional properties to the food. Most seeds are rich in carbohydrates but also contain various minerals and fatty acids. The antioxidant, antidiabetic, anti-bacterial/anti-fungal, anti-inflammatory, anti-hyper cholesterol and anti-proliferative properties were also reported with rambutan and papaya seeds having the most bioactive properties. Novel and conventional extraction methods of the seeds, the functionality of the seeds to improve the food such as pasting and emulsifying properties, and their effect on the colour, texture, sensory and storage stability were also highlighted. In summary, all the selected seeds have the potential to be upcycled as food ingredients as they contain various nutrients while providing therapeutic and functional properties, however, further research can be considered to optimize the seeds’ usability.